PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE KEPALA BERNOMOR BERSTRUKTUR UNTUK MENINGKATKAN MOTIVASI BELAJAR PKN SISWA KELAS VI SDN 029 SUNGAI PINANG KABUPATEN KAMPAR - Dahniar Dahniar (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research was motivated by the low learning motivation of the citizenship education students of the sixth grade studentsof SDN 029 Sungai Pinang Kabupaten Kampar. This study aims to improve the learning motivation of Pkn through theapplication of structured numbered head type cooperative learning models in the sixth grade students of SDN 029 SungaiPinang Kabupaten Kampar. The subjects of this study were all sixth grade students of SDN 029 Sungai Pinang KabupatenKampar, totaling 17 years 2016. The form of research was classroom action research. This research instrument consists ofperformance instruments and data collection instruments in the form of observation sheets of teacher activities and studentactivities. Based on the results of the research and discussion, the application of structured numbered head type learningmodel can improve the learning motivation of the sixth grade students of SDN 029 Sungai Pinang Kabupaten Kampar asseen in the learning motivation of students in the first cycle scored 50% in the low category while in the second cycle got 755% in the very high category In the first cycle this class action research has not been said to be successful while in thesecond cycle the research has succeeded with a success indicator of 75.5% exceeding the performance indicators that havebeen set